If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 9n = 79 Solving 7 + 9n = 79 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 9n = 79 + -7 Combine like terms: 7 + -7 = 0 0 + 9n = 79 + -7 9n = 79 + -7 Combine like terms: 79 + -7 = 72 9n = 72 Divide each side by '9'. n = 8 Simplifying n = 8
| 20x^3+60x^2+25x=0 | | 3x^2+7+8=6 | | c=-5c+-30 | | 3x^2+7+18=6 | | 3/4x-1/3=-8 | | d/-7=-4 | | 2x/6=-10 | | -p^2+p=18 | | 8k-5k=15 | | x^2+56x-406.25=0 | | 3x/9=-9 | | 5X+(-20)=65 | | v=1/3m2h | | -41-3x=9-3x | | 32=h+5 | | 22/3x8(47/8-3/4) | | 12x-3y=108 | | 6x^2+3x+20=0 | | X^2+9x+20=2 | | 4x/9=6 | | 17x+13y=-5 | | 0.05x-3.4=0.4(x-5) | | 3/4*1/4 | | (x+7)/(x+2)=9 | | =36x^6-49x^4+14x^2-1 | | 1/2(x+2)=1/4(2x+4) | | 4+3x=14x+x | | -36=-12+h | | y=-2/5x+40 | | y-(5-2y)=7(y-1)-2 | | 5+1=3 | | 3x+7=3+5x-8 |